2017
DOI: 10.1108/ejtd-06-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

Human resource education in the Middle East region

Abstract: Purpose The purpose of this paper is to provide an overview of human resource development (HRD) education in Middle Eastern countries. In particular, the authors discuss the current state of HRD education, country readiness and challenges that hinder HRD progress in Middle Eastern countries. They argue that HRD programs need to prepare young employees for leadership roles through adapting constructivist pedagogy, including problem-solving, critical thinking and creativity. Design/methodology/approach The des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Apart from gender, another theme which our analysis highlights (see Tables 4, 5 and 6) is that of the influence of Arab culture and values on its management systems (e.g., Ali, 2010;Dirani & Hamie, 2017;Mellahi, 2003). A related focus of research has been to examine the impact of Islamic values, Islamic work ethics and Islamic principles on the management of human resources in the region (see Branine & Pollard, 2010;Budhwar & Mellahi, 2010).…”
Section: Singh and Sharma (2015)mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from gender, another theme which our analysis highlights (see Tables 4, 5 and 6) is that of the influence of Arab culture and values on its management systems (e.g., Ali, 2010;Dirani & Hamie, 2017;Mellahi, 2003). A related focus of research has been to examine the impact of Islamic values, Islamic work ethics and Islamic principles on the management of human resources in the region (see Branine & Pollard, 2010;Budhwar & Mellahi, 2010).…”
Section: Singh and Sharma (2015)mentioning
confidence: 99%
“…Cultural/institutional norms/practices influencing HRM Dirani and Hamie (2017) • Cultural factors impede employees' critical reflection in the workplace in the Middle East.…”
Section: Iles Et Al (2012)mentioning
confidence: 99%
“…As per the study carried out in HRD on education institutions in Middle Eastern countries, it was concluded that educational institutions should equip the students as per the requirements of the modern work places. It is the responsibility of these institutions to equip the students with required skills in order to reduce the skill gap (Dirani & Hamie, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several leadership development strategies such as leadership training workshops, leadership muscle exercises and external quality supervision and assessment of leadership standards have been previously recommended for enhancing outcomes (Preston-Dayne, 2013; Dirani and Hamie, 2017; Borde et al , 2022). Specifically, training and development activities based on the theme of self-development (Table 4) as a leadership development strategy can be adopted by HRD practitioners.…”
Section: Research Implications For Human Resource Development Theory ...mentioning
confidence: 99%